15N-amino sugar stable isotope probing (15N-SIP) to trace the assimilation of fertiliser-N by soil bacterial and fungal communities. (November 2019) - Reay, Michaela K.; Charteris, Alice F.; Jones, Davey L.; Evershed, Richard P.
Abstract: Although amino sugars represent a major component of soil organic nitrogen (ON), the assimilation of nitrate (NO3 − ) and ammonium (NH4 + ) into amino sugars (AS) by soil bacteria and fungi represents a neglected aspect of the global N cycle. A deeper knowledge of AS responses to N fertiliser addition may help enhance N use efficiency (NUE) within agricultural systems. Our aim was to extend a sensitive compound-specific 15 N-stable isotope probing (SIP) approach developed for amino acids (AAs) to investigate the immobilization of inorganic N into a range of amino sugars (muramic acid, glucosamine, galactosamine, mannosamine). Laboratory incubations using 15 N-ammonium and 15 N-nitrate applied at agriculturally relevant rates (190 and 100 kg N ha −1 for 15 NH4 + and 15 NO3 −, respectively) were carried out to obtain quantitative measures of N-assimilation into the AS pool of a grassland soil over a 32-d period. Using gas chromatography-combustion-isotope ratio mass spectrometry (GC-C-IRMS) we found that δ 15 N values for individual AS reflected differences in routing of the applied ammonium and nitrate. The contrasting N-assimilation dynamics of bacterial and fungal communities were demonstrated through determinations of percentage 15 N incorporation into diagnostic AS. N-assimilation dynamics of the bacterial community were altered with the applied substrate whilst fungal N-assimilation dynamics were unaffected. Rates and fluxes of the applied N-substrates into the bacterial AS pool reflected known biosynthetic pathways for AS, with fungal glucosamine appearing to be biosynthetically further from the applied substrates than bacterial glucosamine due to different turnover rates. This sensitive and specific compound-specific 15 N-SIP approach using AS, building on existing approaches with AAs, enables differentiation of N-assimilation dynamics within the microbial community and assessment of microbial NUE with agriculturally relevant fertilisation rates. Graphical abstract: Image 101300 Highlights: 15 N-SIP using agriculturally relevant N rates and low 15 N-enrichments did not perturb the AS pool. δ 15 N values of AS reflected fundamental biochemical differences in assimilation of N-fertilisers. 15 N-incorporated into bacterial AS reflected known fundamental biosynthetic pathways and proximity to 15 N- fertilisers. Bacterial and fungal AS 15 N-assimilation trends showed different temporal responses within the SMC.